2010
DOI: 10.1159/000315656
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fetal Growth Velocity and Smallness at Birth on Adrenal Function in Adolescence

Abstract: The hypothalamic-pituitary-adrenal axis is susceptible to programming during fetal development and may be linked to risk of disease later in life. In a former prospective study the cohort was divided into those born appropriate for gestational age (AGA) or small for gestational age (SGA; birth weight <10 percentile). In 52 adolescent boys (17.5 years) we assessed circulating androgen levels (T, Δ4-adione, DHEAS), overnight serum cortisol profiles (every 20 min), ACTH stimulation test (250 µg i.v.) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
2
7
0
Order By: Relevance
“…In agreement with our findings, Jensen et al [36] reported similar serum DHEAS levels in full-term born 17-year-olds, and Allvin et al [38] in about 20-year-old SGA and AGA men. Jaquet et al [39] also reported similar serum DHEAS and androstenedione levels in 20-year-old full-term born SGA and AGA women.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with our findings, Jensen et al [36] reported similar serum DHEAS levels in full-term born 17-year-olds, and Allvin et al [38] in about 20-year-old SGA and AGA men. Jaquet et al [39] also reported similar serum DHEAS and androstenedione levels in 20-year-old full-term born SGA and AGA women.…”
Section: Discussionsupporting
confidence: 93%
“…A recent study on very preterm born and growth-restricted young adults reported higher DHEAS concentrations compared to the control subjects [23]. SGA children at prepubertal and pubertal age have been shown to have increased DHEAS levels in several [10,11,12,13,14] but not in all studies [35,36]. In the study of Boonstra et al [35], the SGA born children were selected on the basis of short stature at the age of 3–9 years.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, we believe that potential bias of IUGR on suggested DHEA‐S values was excluded. Additionally, findings of several previous studies also did not confirm associations between SGA status and premature adrenarche/serum DHEA‐S levels . Similarly in follow‐up studies of SGA cohorts, very few SGA‐born children have been reported to develop premature adrenarche …”
mentioning
confidence: 79%
“…Additionally, findings of several previous studies also did not confirm associations between SGA status and premature adrenarche/ serum DHEA-S levels. [6][7][8] Similarly in follow-up studies of SGA cohorts, very few SGA-born children have been reported to develop premature adrenarche. 9 Ahmet Ucar also indicated that due to DHEA-S and androstenedione being week androgens, the validity of the serum DHEA-S cut-off values at the transition from PH1 to PH2 suggested by Guran et al warrants reconsideration and that such a cut-off value is only possible with a longitudinal study.…”
mentioning
confidence: 99%
“…The results from studies relating birth weight to DHEAS or IGF-I levels in late adolescence and adulthood were not consistent (Beck Jensen et al 2011;Jaquet et al 1999;Poole et al 2011;Ruder et al 2011;Szathmári et al 2001;Tworoger et al 2006). Here, we investigate this association in late adolescence.…”
Section: Introductionmentioning
confidence: 95%